Exploring Malay Parenting Patterns and Cultural Identity in Medan City: Traditions, Values, Adaptation in an Urban Context - H, Athirah Salsabila; Priscila, Eunice; Zai, Imel Lestari; Tobing, Tessalonika Br. L (Lembaga Riset Mutiara Akbar, 2024)
This research explores early childhood parenting patterns and Malay culture in Medan City, Indonesia. With a focus on traditions, values, and adaption in urban context, this research explores how Malay culture remains relevant in child-rearing patterns amidts dynamic changes in the urban environment. The research method involved in-depth interviews with parents and Malay community leaders living in Medan City, as well as observations of child-rearing practices in everyday life. The research results show that despite adaption to urban development, Malay cultural traditions and values remain the main basis for parenting patterns. However, there are also challenges faced in maintaining Malay cultural identity in globalization and modernization. The implication of this research is the importance of understanding the dynamic of local culture in a urban context to strengthen cultural identity and enrich the study of child-rearing patterns in Indonesia.